Chromosome-level genome sequencing and assembly of the parasitoid wasp Leptopilina myrica - Zhi Dong; Zixuan Xu; Junwei Zhang; Yulong Guo; Qichao Zhang; Lan Pang; Ting Feng; Wenqi Shi; Yifeng Sheng; Jianhua Huang; Jiani Chen (Scientific Data)
Abstract Leptopilina wasps are crucial for biological pest control, particularly against the globally emerging pest Drosophila suzukii. Despite their ecological significance, the genomic basis of host selection and parasitism in this genus remains underexplored. In this study, we assembled a high-quality, chromosome-level genome of Leptopilina myrica, a species collected in Taizhou, Zhejiang Province, China. We employed a combination of PacBio long-read sequencing, Illumina short-read sequencing, and Hi-C technology to produce a genome assembly of approximately 462.30 Mb, with a scaffold N50 of 47.32 Mb and a contig N50 of 4.07 Mb. By comparing the protein-coding genes of L. myrica with those of other Hymenoptera species, we gained insights into the evolutionary history of parasitoid wasps. This high-quality genome will provide a foundation for future research on the genetic and functional traits of parasitoid wasps, shedding light on the evolutionary dynamics of host-parasite interactions. The genome of L. myrica provides a valuable resource for future studies on host-parasite interactions and the genetic basis of parasitoid wasp biology.